The influence of monetary policy on the formation of oil prices (Journal of Economic Research & Business Administration, 2024)
The relationship between monetary uncertainty and price volatility in the global crude oil market has attracted considerable attention in recent years. Understanding this relationship is extremely important for both policy makers and market participants and investors. The purpose of this article is to explore a modern approach to regime switching in order to shed light on the dynamic interaction between monetary uncertainty and price volatility in the crude oil market. If we consider that oil is one of the main sources of energy in the world, and the price of oil plays an important role in the global economy, then the formation of oil prices depends on many factors, including supply and demand, political stability in the production regions, geopolitical events, climate change and, of course, monetary policy. The scientific significance of the article lies in the fact that it allows for a deeper understanding of the relationship between the economic policy of central banks and the dynamics of commodity prices. The practical significance lies in the fact that understanding the impact of monetary policy on oil prices can be useful for both government agencies and businesses.In this research methodology, an empirical method of work was used, in which the influence of monetary uncertainty on the volatility of world crude oil prices was considered. We also touch upon the issue of political uncertainty on the price of oil during the pandemic. The relevance of this article lies in the fact that the price of oil is one of the key indicators for the global economy, the study of the impact of monetary policy on this market is important. The price of oil can influence monetary policy in various ways. For example, changes in the interest rates of central banks affect investors and their decisions to invest in oil companies. In addition, monetary policy also affects the exchange rate, which also has an impact on the price of oil. In conclusion, it can be said that studying the impact of monetary policy on oil prices is important for both science and practice, and may lead to the development of more effective methods of economic and business management.Key words: monetary policy, oil price uncertainty, crude oil, stock market, system modernization, political uncertainty, COVID-19.